Giải phương trình sau : `x^2+3x+2=0`

Giải phương trình sau : `x^2+3x+2=0`

2 bình luận về “Giải phương trình sau : `x^2+3x+2=0`”

  1. x^2+3x+2=0
    x^2+x+2x+2=0
    x(x+1)+2(x+1)=0
    (x+1)(x+2)=0
    ⇒\(\left[ \begin{array}{l}x+1=0\\x+2=0\end{array} \right.\) 
    ⇒\(\left[ \begin{array}{l}x=-1\\x=-2\end{array} \right.\) 
     

    Trả lời
  2. Giải đáp: x=-2; x=-1
     
    Lời giải và giải thích chi tiết:
    x²+3x+2=0
    ⇔x²+2x+x+2=0
    ⇔x(x+2)+(x+2)=0
    ⇔(x+1)(x+2)=0
    ⇔\(\left[ \begin{array}{l}x+2=0\\x+1=0\end{array} \right.\) 
    ⇔\(\left[ \begin{array}{l}x=-2\\x=-1\end{array} \right.\) 

    Trả lời

Viết một bình luận

Câu hỏi mới